Opening Channels to the Eastern Bloc: The First Indonesia-Yugoslavia Trade Contacts, 1953-1956 - Siti Nurdianti (UNIVERSITAS MUHAMMADIYAH METRO, 2027)
This study aims to explain the dynamics of trade diplomacy between Indonesia and Yugoslavia during the period 1953–1956 as part of Indonesia’s early efforts to expand its trade relations with Eastern Bloc countries after independence. This research employs the historical method combined with an economic diplomacy approach to analyze the interplay between foreign policy and national economic interests. The findings show that, in the early 1950s, Yugoslavia was still terra incognita within Indonesia’s foreign trade landscape. In response, the Indonesian government dispatched a trade mission led by R.A. Asmaun to penetrate the Eastern European market and secure new trading partners at a time when industrial expertise was urgently needed to support national economic rehabilitation programs. An important milestone was achieved through the 1953 Trade and Payment Agreement, which formed the basis for a goods exchange valued at 7.25 million USD and opened the way for further cooperation in industrial development, machinery, and infrastructure projects.